Reassessing State Responsibility for the Protection of Internally Displaced Persons Under Contemporary International Law: Normative Evolution, Implementation Gaps, and Accountability Mechanisms - Gerard Tresor V Ngueumaga Kameni (European Scientific Journal, ESJ, 2025)
Internally displaced persons (IDPs) represent a growing global challenge, occurring within the borders of sovereign States. Contemporary international law establishes that States hold primary responsibility for their protection, yet significant gaps remain between legal norms and practice. This article reassesses State responsibility for IDPs, examining international frameworks such as the Guiding Principles on Internal Displacement, the Kampala Convention, and relevant human rights and humanitarian law obligations. It highlights persistent challenges, including selective compliance, weak domestic implementation, and limited accountability mechanisms. The article argues that bridging these gaps requires stronger national legal frameworks and clearer international enforcement measures, ensuring that States fulfill their duties to prevent displacement, protect affected populations, and provide durable solutions. By moving beyond declaratory norms, the protection of IDPs can be strengthened under contemporary international law.